INFLUENCE OF INDEPENDENT CLASSES USING GYMNASTIC EXERCISES ON STUDENTS’ PHYSICAL QUALITIES AND BODY MASS COMPOSITION - Kosynskyi, E. O.; Dyshko, O. L.; Severina, L. Ye.; Sitovskyi, A. M.; Tabak, N. V. (Rehabilitation and Recreation, 2023)
The purpose – to analyze the impact of performing sets of gymnastic exercises during independent classes on the development of flexibility, coordination abilities and body weight composition in students. Material and methods. In the process of research, such methods as analysis of scientific and scientific-methodical literature, pedagogical experiment, statistical analysis, comparison were used. The analysis of the literature proved the relevance of the outlined problem and formed the basis for comparing the results of the experiment. The pedagogical experiment included flexibility testing using the state flexibility test “Bending the body forward from a sitting position”; coordination abilities – with the help of the “Shuttle Run 4×9” test; components of body weight – using the method of bioelectrical analysis of total body resistance (BIA) using a Tanita scale. The material for the study was the results of examinations of 35 first-year students (19 girls and 16 boys). At the beginning of the experiment, the level of development of flexibility, coordination abilities and component composition of body weight (fat and muscle components) was determined. After two months of daily performance of the complex consisting of 11 gymnastic exercises, repeated tests were conducted. The statistical analysis involved several aspects. Statistical analysis was performed using the STATISTICA 10.0 program. During the description of quantitative indicators that have a normal distribution, the obtained data were combined into variational series, in which arithmetic mean values (M) and standard deviations (SD) of the limits of the confidence interval (95 % CI) were calculated. The Student’s t-test was calculated based on the comparison of average values in normally distributed sets of quantitative data. The obtained values were evaluated by comparison with critical values. Paired Student’s t-test was used in the process of comparing averages calculated for related samples. Differences in indicators were considered statistically significant at a significance level of p < 0.05. Nominal data were described with absolute values and percentages. Results. The greatest changes were found in the development of flexibility, the test “Bending of the torso forward from a sitting position” was used, the indicator was 35.19 %. The least influence of self-training is observed on fat and muscle components of body weight. Analyzing the correlations between indicators, reliable connections between dexterity and the fat component were found both before the experiment p = 0.756 and after p = 0.778. Conclusions. Performing gymnastic complexes during independent classes had a significant effect on improving the physical qualities of flexibility and coordination abilities and had a minor effect on the component composition of body weight (fat and muscle components).